Microfluidic Chemical Cytometry of Peptide Degradation in Single Drug-Treated Acute Myeloid Leukemia Cells - Kovarik, Michelle L. (2013)
Microfluidic systems show great promise for single-cell analysis, but as these technologies mature their utility must be validated by studies of biologically-relevant processes. An important biomedical application of these systems is characterization of tumor cell heterogeneity. In this work, we used a robust microfluidic platform to explore the heterogeneity of enzyme activity in single cells treated with a chemotherapeutic drug. Using chemical cytometry, we measured peptide degradation in the U937 acute myeloid leukemia (AML) cell line in the presence and absence of the aminopeptidase inhibitor Tosedostat (CHR-2797). Analysis of 99 untreated cells revealed rapid and consistent degradation of the peptide reporter within 20 min of loading. Results from drug-treated cells showed inhibited, but on-going degradation of the reporter. Because the device operates at an average sustained throughput of 37 ± 7 cells/h, we were able to sample cells over the course of this time-dependent degradation. In data from 498 individual drug-treated cells, we found a linear dependence of degradation rate on amount of substrate loaded superimposed upon substantial heterogeneity in peptide processing in response to inhibitor treatment. Importantly, these data demonstrated the potential of microfluidic systems to sample biologically-relevant analytes and time-dependent processes in large numbers of single cells.